1977
DOI: 10.1002/jlac.197719770812
|View full text |Cite
|
Sign up to set email alerts
|

Eine neue, bequeme [2.2]‐Kronenether‐Synthese; Vergleich verschiedener Detosylierungsmethoden

Abstract: Eine gegenuber der bisherigen Synthese (uber das Lactam 7) des [2.2]-Kronenethers 1,4,10,13-Tetraoxa-7,16-diazacyclooctadecan (1) einfachere und raschere Synthese durch Umsetzung der 1,8-Di-O-tosylverbindung 9 mit der entsprechenden 1,8-Di-N-tosylverbindung 6 und anschlieBende Tosylabspaltung wird beschrieben. Das neue Verfahren umgeht die Darstellung der 1 ,6-Dicarbonsiiure 3 und ihres Chlorids 4; die Ausgangsmaterialien sind leicht zuganglich ; die Cyclisierung wird ohne Anwendung des Verdunnungsprinzips in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Different methods to remove the iV-tosyl blocking groups were tried, including HBr/phenol, H2S04, LiAlH4/THF, and NaAlH2(OCH2CH2OCH3)2. 164 The yields of this last step varied as a function of the number of tosyl groups and the size of the macrocycle. With a triaza-12-crown-4, it was found that HBr/phenol was the best detosylating reagent followed by H2S04 and LiAlH4.…”
Section: A°w°amentioning
confidence: 99%
See 1 more Smart Citation
“…Different methods to remove the iV-tosyl blocking groups were tried, including HBr/phenol, H2S04, LiAlH4/THF, and NaAlH2(OCH2CH2OCH3)2. 164 The yields of this last step varied as a function of the number of tosyl groups and the size of the macrocycle. With a triaza-12-crown-4, it was found that HBr/phenol was the best detosylating reagent followed by H2S04 and LiAlH4.…”
Section: A°w°amentioning
confidence: 99%
“…With a triaza-12-crown-4, it was found that HBr/phenol was the best detosylating reagent followed by H2S04 and LiAlH4. 164 Tabushi and co-workers reported a general synthetic procedure to prepare the polyaza-crown compounds by reacting a polyamine and the dimethyl ester of an oligoglycolic acid followed by reduction of the resulting cyclic diamide (method AH).136,137-178 This method uses…”
Section: A°w°amentioning
confidence: 99%
“…Lithium aluminum hydride is reported to be an effective reagent for sulfonamide removal (25), but it is inappropriate for 8 or 10 as the carboxamides would undergo reduction as well. Dissolving metal reductions using sodium amalgam (15,21,26), or Li or Ca (21) in liquid ammonia, are other reductive cleavage reagents.…”
Section: Ligand Synthesismentioning
confidence: 99%
“…(Bergman andBrynolf, 1989) 82, 115, 708, 720, 751 Brzezinska, E. (Brzezinska and Glinka, 1986) 456, 467 Brzozka, Z. 303, 345 Buhleier, E. (Buhleier et al, 1977) 158, 159, 160, 163, 164, 167, 253, 341; 336, 341; (Buhleier et al, 1977) 358, 368, 397; (Buhleier et al, 1978) 394, 397, 435,467 Bujewski, A. (Biernat et al, 1979) 45, 66, 137, 166, 418, 420, 452, 453, 467, 515, 527, 528,534 49, 63, 69;(Martinet al, 1982) 49, 70, 129, 130, 146, 170;(Martin and Bulkowski, 1982) 131, 170;(Martinet al, 1982) 359, 399;(Bulkowski et al, 1977) 473, 533, 534; 553, 688; 667, 668, 682; (Martin and Bulkowski, 1982) 667, 668, 688 (Izatt and Christensen, 1978) 4, 25;(Izatt and Christensen, 1987a) 4, 1 I , 25; (Izatt and Christensen, 1987b) 4, 1 I , 25; ; (Bradshaw et a]., 1989b) 20, 23; (Bradshaw et al, 1976) 31, 66; Christensen, J .…”
mentioning
confidence: 99%